Kedudukan Anak Yang Menjadi Korban Terjadinya Tindak Pidana Pencabulan Dalam Pandangan Viktimologi - Diaz Riady Bukoting; Dian Ekawaty Ismail; Avelia Rahmah Y Mantali (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
This study aims to find out about the position of children who are victims of sexual abuse in view of Victimology. The method used in this study is empirical with qualitative descriptive data analysis that describes and outlines the data and facts of the field. The results of this study show that child abuse is one of the most destructive forms of crime, and often has a long-term impact on victims of abuse. Victimology, in its view as the study of victims of crime, plays an important role in understanding the impact of child abuse, as well as in designing effective treatment and protection approaches.. The protection of children is very important because its violation is a violation of human rights. It can be seen that the position of children towards victims of abuse in the view of victimology provides a better view of victims of crime as a result of human actions that cause mental, physical and social suffering.